The Effect of Board Composition on Conservatism: Empirical Evidence from Tehran Stock Exchange (TSE) - Heydari, Keramat Ollah; ., Saber Samadi; ., Hamid Asadzadeh; ., Ahmad Kazemi Margavi; ., Hemad Nazari (Journal of Education and Vocational Research, 2012)
Conservative is misinterpreted as capturing accountants ’tendency to require higher degree of verification for recognizing good news than bad news in financial statements. Under this interpretation of conservatism, earnings reflect bad news more quickly than good news. By using firms’ stock returns to measure news, the asymmetric time lineless of recognizing good news and bad news can be examined as a measure of conservative behavior and as them an in question of this research in Irani and capital market. This research examines effect of composition of the board of directors of the companies listed in Tehran Stock Exchange (TSE) on conservative. Data analysis for seven years (2003-2010) shows that companies with a more in dependent board are more conservative. It means that these companies report bad news more timeliness than good news. The results of the research results confirm and reinforce previous researches.